Macrophage Flipping from Foe to Friend: A Matter of Interest in Breast Carcinoma Heterogeneity Driving Drug Resistance - Tandon, Ishita; Sharma, Nilesh K. (Current Cancer Drug Targets, 2019)
Tumor heterogeneity within various cancer types including breast carcinoma is pivotal in the manifestations of tumor hallmarks. Tumor heterogeneity is seen as a common landscape where intra-tumoral components including cellular and non-cellular factors create an interface with outside environment that leads to the unique identity of a specific cancer type. Among various contributors to tumor heterogeneity, cellular heterogeneity immensely plays a role in drug resistance and relapse of cancer. Within cellular heterogeneity of tumor, tumor-associated macrophages (TAMs) are the pro-tumor type of immune cells that promote growth, metastasis and drug resistance in breast carcinoma and other cancer types. Revealing the molecular aspects of TAMs can provide a breakthrough to remove therapeutics blockade to existing drugs and this understanding in future will pave the way for a new class of cancer immunotherapeutic. This review addresses current understanding of the role of TAMs in breast carcinoma hallmarks and clarifies the current scenario of pre-clinical drugs directed to tame pro-cancer TAMs.
Keywords: neoplasms